If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying an = -2 + (n + -1) Reorder the terms: an = -2 + (-1 + n) Remove parenthesis around (-1 + n) an = -2 + -1 + n Combine like terms: -2 + -1 = -3 an = -3 + n Solving an = -3 + n Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Divide each side by 'n'. a = -3n-1 + 1 Simplifying a = -3n-1 + 1 Reorder the terms: a = 1 + -3n-1
| y=x^2-5x-9 | | 7x+y=4x+16y | | 5d^2-10d+h=0 | | (y^4/-2z^2)^4 | | X^2+15x+56.25=26.25 | | 5x-5x=200 | | 9=26+3 | | 4-11=17 | | 6f=6f-24 | | g^2-12gh+35h^2=0 | | 5x-25+x+13=180 | | C=4-3X-4Y+2X^2+3Y^2+XY | | logx^2-3logx=-2 | | d^2=490 | | 2b+3(3b+1)=52 | | -3/4x72 | | -4+24=-24 | | d^2-2d+3h=9 | | 1-7+10=0 | | 2b^3/b^2 | | 4x^2-8x-35=0 | | 3x+(x+5)=-3 | | 3x^2-25+2=10 | | 4lnx=4nx | | -1/2x-4/5 | | -1.47=j+-4 | | 4nx=4lnx | | 1.1+.75x+2=3.1+.75x | | 4g^3-4g^2-24g=0 | | 1/8x-4/5 | | (x^2)-x(b+a)+ab-abx^2=0 | | 4.5x=3.2+4.5x |